Comparison of risk factors for coronary event in people with unattributed and non-coronary chest pain: an electronic health record cohort study. (14th October 2021) - Rathod-Mistry, T; Mamas, M; Bailey, J; Chen, Y; Clarson, L; Denaxas, S; Hayward, R; Hemingway, H; Van Der Windt, D; Jordan, K
Abstract: Background: Patients presenting to primary care with chest pain are often not given a cause. Patients with such unattributed chest pain have an increased risk of future cardiovascular disease (CVD) compared to patients with diagnosed non-coronary chest pain. It is unknown whether risk factors for CVD determined in the general population are the same for the population with unattributed or non-coronary chest pain. Purpose: To determine if key risk factors for a coronary event in patients with unattributed chest pain are similar to those for patients with non-coronary chest pain and previously identified in the general population. Methods: The study used primary care information from the Clinical Practice Research Datalink Aurum linked to hospital inpatient and mortality data. Patients aged ≥18 years with an incident record of unattributed or non-coronary chest pain in 2002–2018 and no diagnosis of CVD were included. We included as potential risk factors those established for CVD in the general population and non-coronary explanations for chest pain. Flexible parametric models estimated hazard ratios (95% confidence intervals (CI)) between factors and incident coronary event (defined as myocardial infarction, angina, coronary heart disease, percutaneous intervention, and coronary artery bypass graft surgery). Results: There were 375, 240 patients with unattributed chest pain (53% female: mean age 49; 47% male: mean age 47) and 245, 329 patients with non-coronary chest pain (58% female: mean age 47; 42% male: mean age 44). Median duration of follow-up was 5 years. In the unattributed chest pain group, there were 111 (95% CI: 109, 112) and 140 (138, 142) coronary events per 10, 000 person-years in females and males, respectively. Lower rates of coronary event were observed in the non-coronary chest pain group (females: 73 (72, 75); males: 96 (94, 98)). Within females (Figure), in both chest pain groups the strongest risk factors were type I and type II diabetes, atrial fibrillation, and hypertension whereas no associations were observed for migraine and chronic kidney disease. Whilst alternative explanations for non-coronary chest pain also increased the risk of coronary events, associations were less strong than for established general population risk factors. Similar findings were found in males although family history of coronary event was a stronger risk factor in the non-coronary chest pain group compared to the unattributed chest pain group. Conclusions: The pool of factors found to increase the risk of coronary events in patients presenting with recorded unattributed or non-coronary chest pain are similar but not identical to those identified for the general population. Further research is needed to develop prognostic models to identify patients at the most risk of a coronary event as models developed in the general population are unlikely to be applicable given the increased underlying risk of coronary events in these populations. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Study funded by the British Heart Foundation, reference PG/19/46/34307. KJ also supported by matched funding awarded to the NIHR Applied Research Collaboration (West Midlands).